Trade and development in a labor surplus economy - Edward B. Barbier; Michael Rauscher (Universität Rostock, Institut für Volkswirtschaftslehre, 2005)
This paper looks at a model in which two countries trade agricultural and manufactured commodities. The manufactured-goods sector produces with increasing returns to scale under conditions of monopolistic competition. It is shown that an increase in land endowment (or an increase in agricultural productivity) can have negative welfare implications for both countries. This outcome can result under three different scenarios: asymmetries across countries, i.e. a North-South model, a neoclassical labor market in the home country's instead of a Lewisian market, and alternative utility functions.
Keywords: F12; J61; O15; O18; 330; international trade; labor surplus economy; land expansion; monopolistic competition; North-South model